Fetomaternal Outcome in Antepartum Hemorrhage After 34 Weeks of Gestation - Ranabhat, Bijay Kumar; Dangal, Ganesh; Poudel, Sandesh; Adhikari, Shreeprasad; Khadka, Chiranjivi (Journal of Nepal Health Research Council, 2024)
Background: Antepartum hemorrhage is defined as any bleeding from or into the genital tract during pregnancy, after the period of viability until delivery of the fetus. APH complicates 2-5% of pregnancies and is a primary cause of perinatal and maternal mortality globally. Aim of this study is to evaluate maternal and perinatal outcome in patients with APH at a tertiary care hospital.Methods: The present study was a cross sectional study conducted in Obstetrics and Gynaecology department of Paropakar Maternity and Women’s Hospital, during a period of 5 months from December 2022 to April 2023. 50 cases of APH were enrolled with gestational age ? 34 weeks of gestation.Results: Incidence of APH after 34 weeks of gestation was 0.51%. The most common type of APH was abruption placenta (44%) followed by placenta previa (32%) and undetermined (24%). The age range of 26 to 30 years old accounted for the highest number of APH patients i.e., 21(42%). In placenta previa, 75% and in abruption placenta 63.64% were multigravida. APH was presented mostly between 37-40 weeks. Around 26% of the patients had anemia at the time of admission. Most common mode of delivery was cesarean section (82%). Most common maternal complications were PPH (40%), blood transfusion (28%), DIC (4%), cesarean hysterectomy (4%). Low birth weight and preterm were the most common causes of fetal complications. Maternal mortality was 2% and perinatal mortality was 18% overall.Conclusions: APH is primary cause of maternal and perinatal morbidity and mortality. In our study, an abruption placenta was the most frequent cause of APH. Cesarean section was the most commonly used mode of delivery. PPH with blood transfusion was the most prevalent maternal complication, while fetal complications included low birth weight and preterm..Keywords: Abruptio placenta; antepartum haemorrhage; placenta previa.